Quasi-Static Test Study on Seismic Behavior of Large-Section Fabricated Utility Tunnel. (18th March 2022) - Zhu, Li; Shangguan, Shiqing; Yu, Haitao; Guo, Yawei; Chen, Zheng; An, Dong
Abstract : Based on the urban utility tunnel project in Xiong'an New Area, to clarify the seismic behavior of the utility tunnel structure, the overall structure model of the four-cabin large-section utility tunnel and the quasi-static test of the joint specimens have been completed. The results show the following. (1) The hysteresis curve of the overall structure is relatively full, showing good ductility and energy consumption. The middle joint has better bending performance. The ductility of the side joint is worse than that of the middle one. (2) The skeleton curve of the joint specimen is divided into three stages: obvious cracking, yielding, and ultimate load. After the overall structure reaches the ultimate load, the load curve basically tends to be horizontal. (3) The stiffness degradation of the overall structure and the joint specimens continues to be uniform during the entire loading process. (4) The structural design of the fabricated utility tunnel can ensure the seismic behavior under normal condition.